Treatment and Outcome of Metastatic Renal Cell Carcinoma With Sarcomatoid Differentiation: A Single-Center, Real-World Analysis of Retrospective Data - Janisch, Florian; Kienapfel, Christina; Fühner, Constantin; Klotzbücher, Thomas; Marks, Phillip; Hillemacher, Tobias; Meyer, Christian P.; Iwata, Takehiro; Parizi, Mehdi Kardoust; Sauter, Guido; Fisch, Margit; Shariat, Shahrokh F.; et al. (Frontiers in Surgery, 2021)
Background: Sarcomatoid histology (sRCC) in patients with metastastic renal cell carcinoma (mRCC) is still underresearched in current therapy regimes. We aim to evaluate the impact of sRCC on outcomes in patients with mRCC treated with tyrosine-kinase inhibitors (TKI). Methods: We collected complete data of 262 consecutive mRCC patients from our institutional database for this retrospective study. All patients were treated with TKI within a single or multimodal treatment approach. All analyses adjusted for presence of sRCC. Descriptive statistics as well as uni- and multivariable outcome metrics including progression-free (PFS) and overall survival (OS) as endpoints were performed. Results: Overall, 18 patients had sRCC (6.9%). Patients with sRCC had more often clear-cell histology (p=0.047), a higher T-stage (p=0.048) and underwent cytoreductive nephrectomy more frequently (p<0.001). Most common first-line TKIs were Sunitinib (65.6%), Sorafenib (19.5%) and Pazopanib (10.3%), respectively. At a median follow-up of 32 months, patients with sRCC had significantly reduced PFS (p=0.02) and OS (p=0.01) compared to patients without sRCC. In multivariable analyses that adjusted for effects of standard mRCC predictors, sarcomatoid feature retained its independent association with inferior PFS (HR: 2.39; p=0.007) and OS (HR: 2.37; p=0.001). This association remained statistically significant in subgroup analyses of patients with Sunitinib as first-line therapy (PFS p<0.001; OS: p<0.001). Conclusion: Despite its rare occurrence, our findings confirm sRCC as a powerful predictor for inferior outcomes in mRCC treated with targeted therapies. This suggests a need for more tailored treatment strategies in patients harboring mRCC with sarcomatoid histology to improve oncological outcomes.